Understanding the investor : a Maltese study of risk and behavior in financial investment decisions - Bonello, Antonietta (Emerald Publishing Limited, 2019)
In finance, understanding investors and their motivations is key for any business and policy-maker. Analyzing financial decisions and investor behavior can shed light on the major characteristics and variables behind trading decisions, giving researchers and investors a better understanding of the influences that affect the stock market.Understanding the Investor: A Maltese Study of Risk and Behavior in Financial Investment Decisions offers a nuanced view of the Maltese investor and the Malta Stock Exchange. In this in-depth study, author Antonietta Bonello explores the major risk appetite and tolerance characteristics of decision-taking for local financial investors. With foreign direct investment (FDI) growing by around 21% between 2014-2017, Malta's investment activities can be seen and used as an example of actual investment decisions taken by active investors. Looking across investor expectations, return of income, risk and loss aversions, disposition effect, financial literacy and overconfidence, Bonello offers an exciting perspective on investors in Malta, and the implications of this on the wider financial world.For individual investors and researchers in the area of personal finance, this new case study offers an in-depth look at investor behavior, allowing readers to understand the motivations behind emerging investment trends and to draw far-reaching conclusions on how best to prepare for upcoming challenges in financial investment.